Assessing the effectiveness of the Kampung Keluarga Berkualitas program management in Banjarbaru - Hayati, Safira; Syafari, Muhammad Riduansyah; Shaddiq, Syahrial (Priviet Social Sciences Journal, 2026)
Based on the disparities in the implementation of activities in Quality Family Village (Kampung KB) in each region, this study aims to analyze the effectiveness of the Kampung KB program in Banjarbaru City using a qualitative descriptive approach and comparative methodology. The object of this study is the effectiveness in the management of the Quality Family Village program, while the subject of this study is the manager responsible for the management of the Kampung KB. The results of the study reveal several factors that hinder the implementation of the Kampung KB program, thereby impacting its effectiveness. The KB Village in Guntung Manggis is one of the best Kampung KB, with all Working Groups (POKJA) actively providing guidance. This is despite limited funds and the managers' approach to the community. However, the managers have prioritized activities to ensure they remain effective and have a positive impact on the community, build bonds, and record and listen to the community's complaints and needs in terms of guidance. Meanwhile, Kampung KB Sungai Tiung is still trying to make its activities more effective by minimizing obstacles, particularly the lack of coordination between stakeholders in managing Kampung KB. Furthermore, weak community participation in Kampung KB activities remains an issue that continues to be discussed between managers and the community in an effort to improve the effectiveness of Kampung KB.